English learning achivement in reading comprehension class through digital literacy practices - Zuhri, Fauris (2021)
This study aims to describe how English teachers develop and implement Reading Comprehension Class through digital literacy practices to improve English learning achievement. English teachers play essential roles in gaining the achievement of learning English. The research design is explanatory qualitative method. The study results showed that developing and implementing digital literacy practices can improve English learning achievement. Three reasons come from the advantages of digital technology being more comfortable accessing reading resources/materials, various reading resources/materials are available, and reading resources/materials are updated. Therefore, Reading Comprehension classes are more exciting and challenging. So, this study approved that developing and implementing Reading Comprehension Class through digital literacy practices plays an essential role in enhancing English learning achievement.